ChemInform Abstract: Synthesis of Norbornane Bisether Antibiotics via Silver‐Mediated Alkylation. Issue 32 (August 2015) - Pfeffer, Frederick M.; et al.
Abstract Bisalkylated and bisbenzylated norbornane bisether dicarboxylates are prepared and transformed in three further steps into the corresponding norbornane bisether diguanidines.